68 LNK001 is a High-Fidelity AND-Logic-Gated CAR T Cell Therapy that Enables Precision Targeting of Clear Cell Renal Cell Carcinoma (ccRCC): Target Discovery and Validation for the ATHENA Phase 1 Trial - Alexander Bankovich; Bryan Smith; Colin Farrell; Angeles Estelles; Janette Sutton; Zeynep Wheeler; Kazuteru Hasegawa; Benjamin Bauer; Jakob McBroome; Diego Vargas-Inchaustegui; Regina Lin; Mark Wallet (The Oncologist, 2026)
Abstract Background Chimeric antigen receptor (CAR) T cell immunotherapies have shown exciting clinical benefits in hematologic malignancies, whereas challenges have persisted in addressing solid tumors. A key reason for the lack of success in solid tumors is on-target off-tumor (OTOT) toxicity that has previously occurred towards targets such as CAIX in ccRCC. New tools are required to enable precise targeting of malignant cells and sparing of normal tissues. We have developed Logic-gated Intracellular NetworK (LINK) technology to overcome the OTOT toxicity challenge. The LINK platform is a Boolean AND-gate that requires two antigens to be simultaneously present on the same target cell for CAR T activation and target cell elimination. This creates a novel paradigm for selection of target pairs that only co-occur on the surface of malignant cells even though they may be individually present on normal healthy cells. Methods To identify suitable target pairs, we assembled a rich, highly-curated single-cell RNAseq data set representing over 29 million normal human cells and 390,000 malignant ccRCC cells. We further developed an in silico analytics platform anchored in single-cell RNAseq data that is used to assess target pair co-expression on tumor, versus normal tissue cell types. We scored over 28 million potential cell surface target pairs, generated from approximately 7,500 cell surface proteins, across our curated dataset to assess the quality of this association. Results Through detailed in silico analyses, CAIX and ENPP3 were selected as the highest quality target pair. To validate the pair, IHC and flow cytometry assays were developed to characterize CAIX and ENPP3 expression on malignant and normal cells. IHC and flow cytometry analyzed for co-expression within patients and within each cells, respectively demonstrated a strong therapeutic potential. Further analysis of 419 ccRCC cores shows that the 84% of patients with high CAIX expression are almost universally (99%) high for ENPP3. Conclusions Based on validation of the CAIX and ENPP3 target pair, we developed LNK001 as an AND-logic-gated autologous ex vivo engineered CAR T cell therapy. Binder domains targeting CAIX or ENPP3 were fused to two separate synthetic receptors that utilize SLP76 or LAT signaling domains, respectively. Preclinical studies demonstrate safety and efficacy of LNK001 for selective targeting of malignant CAIX+ ENPP3+ ccRCC cells without OTOT activity against CAIX+ ENPP3- or CAIX- ENPP3+ target cells representing normal tissues. Collectively, these studies form the basis for clinical development of LNK001 in advanced and metastatic ccRCC in a phase 1 clinical trial.